BACTERIAL LOAD IN RELATION TO PHYSICO-CHEMICAL PARAMETERS AND FAECAL INDICATORS OF DRINKING WATER SOURCE - Ćirić, Slavica; Prodanović, Danijela; Milošević, Božidar; Prodanović, Marija (Bulletin of Natural Sciences Research, 2019)
The aim of this study was to examine the relationship between bacterioplankton and physico-chemical parameters of water that serves as a source of drinking water as well as the relationship between bacterioplankton and the indicators of faecal contamination of water. Bacterioplankton abundance was determined by the cultivation method which included the inoculation of water samples on PCA and R2A media and incubation at 20 °C for 7 days. Total bacterial count was determined by epifluorescence microscopy, and three bacterial morphotypes were distinguished: rods, cocci and curved forms. Bacterial biomass was also determined. Eleven physico-chemical parameters of water were determined: temperature, pH, turbidity, conductivity, UV extinction, KMnO4 consumption, total phosphorus, orthophosphates, ammonium-, nitrite- and nitrate nitrogen. As indicators of faecal contamination, the counts of total coliforms, faecal coliforms, faecal streptococci and sulphite-reducing clostridia were determined. Although there were significantly higher number of bacteria on R2A medium in relation to PCA medium, both media showed significant negative correlation of aerobic mesophilic bacteria with water temperature, in all seasons, and significant positive correlation with UV extinction, turbidity, KMnO4 consumption, total phosphorus, orthophosphates, ammonium nitrogen and nitrate nitrogen. Also, these bacteria showed significant positive correlation with total bacterial count and bacterial biomass, as well as bacterial indicators of faecal contamination.
Keywords: Drinking water; Physico-chemical parameters; Aerobic mesophilic bacteria; Faecal indicators